The application of chicken slaughter concept by Islamic law at slaughterhouses in Johor - Mohamad Rafi, Mohmad Shah (2014)
Halal chicken slaughtering is crucial for all Muslims around the world. Hence, poultry slaughterhouse managements need to guarantee that Islamic law being applied in poultry slaughtering as embraced in Al-Quran and Hadith. Lamentably the rate of chicken slaughter premises which got halal accreditation from the Jabatan Kemajuan Islam Malaysia (JAKIM) and the Jabatan Agama Islam Negeri (JAIN) is low. This study was conducted to identify the application of the halal slaughtering concept as indicated by Islamic Law, taking into account four fundamental variables which poultry slaughterhouse managements, works procedures in slaughterhouses, the poultry slaughter process and poultry slaughtering equipment. This study was conducted in the Pontian area, with the number of respondents that was 19 among poultry slaughterhouse managers. A questionnaire was utilized as the research instrument. The review information was examined using Statistical Package of The Social Science Version 16.0 (SSPS 16.0) and presented in the form of frequency, percentage and mean. The study showed that chicken abattoir manager who have not received accreditation of halal certiﬁcate, on the average did not meet a number of legitimate standards and conditions of halal slaughtering. Thus, the ﬁndings of this study show that the managers are not applying the concept of halal in chicken slaughtering. In reality, the managements of poultry slaughter premises were at a moderate level of the mean value of 1.433. As to improve this study, qualitative research design using observation as a method for information gathering propose for further study